Analisis Kurikulum dalam Perspektif Islam: Kajian terhadap Konsep, Komponen, dan Implementasi Kurikulum Pendidikan Islam - Alfina Nadzira (LPPI Yayasan Almahmudi bin Dahlan, 2026)
The curriculum is a fundamental component in the educational system that determines the direction, objectives, and content of learning. In the context of Islamic Education, the curriculum functions not only as an academic guide but also as an instrument for shaping the character, faith, and morality of students based on the values of the Qur'an and Hadith. This article aims to analyse the concept of curriculum from an Islamic perspective, identify the components of the Islamic education curriculum, and examine its implementation in Islamic educational institutions in the modern era. This study employs a qualitative method using a literature review approach, analysing various books, academic journals, and relevant literary sources. The findings indicate that the Islamic education curriculum has a strong theological foundation, rooted in divine revelation and the scholarly consensus of Islamic scholars. The components of the Islamic education curriculum include objectives (al-ahdaf), content (al-muhtawa), methods (al-thariqah), and evaluation (al-taqwim), all of which must be aligned with maqashid al-syariah. The implementation of the Islamic education curriculum faces various challenges in the modern era, including the dichotomy of knowledge, limited resources, and a mismatch between the formal curriculum and the needs of society. Therefore, an integrative, comprehensive, and insan kamil-oriented curriculum reform is required to address the challenges of the times